Assessment of Sustainable Ethanolamine-Based Protic Ionic Liquids with Varied Carboxylic Acid Chains as Corrosion Inhibitors for Carbon Steel in Saline Environments - Pascoal, Caio Victor Pereira; Da Silva, Lucas Renan Rocha; Florez, Mauro Andres Cerra; Cavalcante, Thiago Roberto Felisardo; Avila, Julian Arnaldo [UNESP]; Salomão, Francisco Carlos Carneiro Soares; Barros, Eduardo Bedê; Avelino, Francisco; Lomonaco, Diego; Pinheiro, Regiane Silva; de Sant’Ana, Hosiberto; Rezayat, Mohammad; et al. (MDPI, 2025)
The inhibitory performance of three distinct protic ionic liquids (PILs), namely, 2-hydroxyethyl ammonium formate (PIL 01), 2-hydroxyethyl ammonium propionate (PIL 02), and 2-hydroxyethyl ammonium pentanoate (PIL 03), was evaluated to determine their suitability as eco-friendly corrosion inhibitors for carbon steel (ASTM A36) in a 3.5 wt. % NaCl aerated neutral electrolyte solution. Standard corrosion inhibitor assessment methods, including electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), weight loss measurements, and microscopic techniques (SEM and optical microscopy), were employed to examine the steel surface and corrosion rate. There is a general agreement that the inhibition efficacy is directly associated with the adsorption capacity of substances on the surface of an investigated material, normally stainless or carbon steel. The standard free energies of adsorption were approximately −22 kJ mol−1, indicating a physical adsorption type of interaction between ionic liquids and the electrode surface. The adsorption behavior of protic ionic liquids on an A36 steel surface conforms to a Langmuir-type isotherm. In conclusion, PIL 01 demonstrated an inhibition efficiency exceeding 80%, while PILs 02 and 03 exhibited efficacies in the 50–60% range. The inhibition efficiency was observed to be proportional to the inhibitor’s concentration. These results suggest that PIL 01, PIL 02, and PIL 03 exhibit significant corrosion inhibition properties.
Keywords: carbon steel; corrosion inhibitor; electrochemistry; protic ionic liquids; saline environment